THE EFFECTIVENESS OF RELIGIOUS PROGRAMME: ANALYSIS OF SPIRITUALITY PROGRAMME IN PRISON AMONG MUSLIM FEMALE INMATES - Mohamed Jodi, Khairul Hamimah; Mohamad, Mohd Afifuddin; Mohamad, Mohammad Taqiuddin (Journal of Al-Tamaddun, 2015)
This paper attempts to examine the prison institution with the effort to identify Islamic-based program through a program which cater the halaqah modules in the prison. Halaqah programme is an approach to treat and rehabilitate inmates so that they have the opportunity and space to transform themselves from an immoral to a morally behave person. For this study, the Kajang Women's Prison, Selangor has been chosen as the premise of the study. Respondents were selected with a snowball sampling method in which the focus group consisting of five people aged 21 to 50 years, and involved in the Halaqah programme for six months and above. Interviews as well as observations were used to obtain research data. Data were analyzed by using thematic content analysis and the data separation was done based on specific themes, such as knowledge of faith, fiqh, sirah/akhlak, the Qur'an and the Hadith. The results showed a lack of knowledge and religiousity causes them to get involved in the social problems. In addtition, they were influenced by negative factors that include socio-economic instability and stress of modern lifestyle. The study also found that Halaqah programme has been successful in achieving its' objective as a core treatment for Muslim female inmates.